Applying item based on Collaborative filtering method of building plan aplication at ketintang surabaya SMK library in web system - Imaddudin Al- Asfahani; Sulistiowati Sulistiowati; Vivine Nurcahyawati (Jurnal Sistem Informasi Universitas Dinamika, 2021)
SMK Ketintang is one of the vocational high schools in Surabaya. SMK Ketintang Library to support the process of teaching and learning activities for students, namely the library. The existence of a library is helpful to add or increase knowledge for students. Nowadays there are problems in libraries, namely when collecting book data, borrowing and returning books, librarians still use papers. In addition, when members decide what books to borrow members have to search for books on the shelves directly, members need more time when searching for books to be borrowed. In addition, because there is out of stock collection of books, the library section sometimes get difficult to provide book recommendations according to student needs. Based on these problems, the solution obtained is by making a web-based application using the item-based collaborative filtering method which can help the library business process become more structured in one application and provide book recommendations to members who are looking for or will borrow books. The method of implementing this method is applied, namely reading data from the loan history. Then the data is processed using this method as to produce data output book recommendations that have never been borrowed by members.